Utilização de modificador orgânico e efeito do gênero na recria de bovinos do composto São Marcos em pastagem de inverno - Ghinzelli, Fabrício (2019)
The objective of this work was to evaluate animals of the são marcos bovine composite (½ Marchigiana + ½ Aberdeen Angus) in winter pasture rearing phase. The pasture used was an oat intercropping with ryegrass on a farm in the Iguaçu Valley Region, PR - Brazil. Anorganic modifier was also used and analyzed if there was any difference in animal performance. Thirty-six animals with an age of approximately 8 months were used and the weight gain of males (n = 14) and females (n = 22) was compared. An injection, subcutaneous, of 10 mL of the product (BRAVET organic modifier) was applied to 12 females and 7 males, approximately every 30 days, along with the weighing of all animals to gauge the weight gain per animal and its average daily gain during each grazing period. The area used was 15.8 hectares, the pasture was planted with seeder, in line, on 10/04/2018. The sowing density was 62 kg (oats) and 20 kg (ryegrass)/hectare. The group that received organic modifier showed gains in 95 days of grazing similar to the control group (64.29 vs. 63.96 kg). However, males gained more weight (p<0.0001, by the Tukey test), 73 kg (768 g / day), than females, 55.2 kg (581 g / day). Also, the daily weight gain potentials were evaluated in 3 periods after pasture implantation, period (P) 1 (day 46 to 74), P2 (day 75 to 111) and P3 (day 148 to 178). Gains per day were 875, 581 and 633 g for P1, P2 and P3, respectively. The average daily weight gain in P1 was higher (p<0.0001) than in the other periods. Thus it can be concluded that the first 30 days of oat and ryegrass grazing allow high daily weight gain, after these gains decrease considerably, but remain constant until the end of this forage consortium cycle. The application of injectable organic modifier is not indicated to increase the weight gain in the rearing phase of european beef cattle managed in oat and ryegrass pasture. In oat and ryegrass pasture, bovine males gain more weight than females in the rearing phase.